Aryl- and silyl-substituted silyliumylidene ions in the hydrosilylation of CO2 - Stigler, Sebastian; Thorwart, Thaddäus; Greb, Lutz; Inoue, Shigeyoshi (ChemCatChem, 2025)
Tetryliumylidene ions, stabilized by N-heterocyclic carbenes (NHCs), have emerged as promising main-group catalysts for the reduction of carbon dioxide (CO2). Herein, we report the catalytic activity of aryl- and silyl-substituted silyliumylidenes (1 - 4) in the hydrosilylation of CO2 with diphenylsilane at room temperature, using acetonitrile as solvent. With a low catalyst loading of 5 mol%, full conversion of diphenylsilane was achieved within a moderate reaction time, yielding a mixture of silylformate, bis(silyl)acetal, and silylated methanol. Mechanistic studies, supported by nuclear magnetic resonance (NMR) spectroscopy and density functional theory (DFT) calculations, suggest that the silyliumylidene ions act as precatalysts, forming sila-acylium ion intermediates that subsequently generate the catalytically active siloxy-silylene species. These findings highlight the potential of NHC-stabilized silyliumylidene ions as efficient and selective main-group catalysts for CO2 hydrosilylation.
Online veröffentlicht: 9. November 2025
Gesehen am 03.02.2026
Im Titel ist die Zahl "2" tiefgestellt